Professional Skills in International Financial Surveillance: Assessing Change in IMF Policy Teams. Issue 2 (1st July 2014) - Seabrooke, Leonard; Nilsson, Emelie Rebecca
<x xml:space="preserve">Abstract</x> In 2006, the International Monetary Fund's (IMF) Financial Sector Assessment Program (FSAP) lauded Iceland's capacity to "withstand extreme, but plausible, shocks, " which was clearly an error in judgment. After the international financial crisis hit, IMF officials bemoaned the lack of professional market skills in FSAP teams. Importing these skills was difficult given IMF staff freezes, but postcrisis FSAP continued with heightened legitimacy inside and outside the IMF. This article provides an assessment of FSAP teams, focusing on the hiring of external experts and their professional skills. We use an Optimal Matching analysis of work roles in career histories to identify differences in policy teams and external experts' attributes. The article also draws on interviews with FSAP team members from 2008 to 2013. We demonstrate that changes in professional skills and team composition are a consequence of demands for professional insulation, institutional legitimation, and a view of professionalism as transnational organizational competence.